Literasi Zakat Hasil Perkebunan Kelapa Sawit - Nora Septini Harahap; Zulaika Matondang; Delima Sari Lubis (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Padangsidimpuan, 2021)
ABSTRACT South Labuhanbatu Regency is one of the largest fresh fruit bunch producing areas in Indonesia with the majority of the population being Muslim, so South Labuhanbatu Regency should have a large zakat potential for oil palm plantations in South Labuhanbatu Regency. Apparently, not in line with the expectations that occur in the field with the low level of literacy among oil palm farmers, causing delays in the distribution of zakat funds that should be paid annually, this makes zakat on plantation products or commonly referred to as zakat on assets still taboo among the people of Labuhanbatu district. South especially oil palm farmers. This should be a concern for everyone considering that zakat is not only a pillar of Islam that must be implemented, but zakat is also one of the most effective poverty alleviation instruments by developing productive zakat for the poor and needy. The zakat institution, BASNAZ, in South Labuhanbatu Regency, should take a look at this and take concrete actions in increasing zakat literacy for oil palm plantations in South Labuhanbatu Regency. Keywords: Literacy, Zakat, BAZNAS ABSTRAK Kabupaten Labuhanbatu Selatan merupakan salah satu daerah penghasil tandan buah segar terbesar di Indonesia dengan mayoritas penduduk beragama muslim, dengan begitu seharusnya kabupaten Labuhanbatu Selatan memiliki Potensi zakat perkebunan kelapa sawit yang besar di kabupaten Labuhanbatu Selatan. Ternyata, tidak sejalan dengan ekspetasi yang terjadi di lapangan dengan rendahnya tingkat literasi di kalangan para petani kelapa sawit menjadikan tersendatnya penyaluran dana zakat yang seharusnya ditunaikan setiap tahunnya, hal tersebut menjadikan zakat hasil perkebunan atau biasa disebut dengan zakat harta masih tabu di kalangan masyarakat kabupaten Labuhanbatu Selatan terutama para petani kelapa sawit. Sudah seharusnya hal ini menjadi perhatian setiap kalangan mengingat bahsanya zakat tidak hanya merupakan rukun islam yang wajib dilaksanakan namun, zakat juga merupakan slah satu instrument pengentas kemiskinan yang paling ampuh dengan mengembangkan zakat produktif pada kalangan fakir dan miskin. Sudah seharusnya lembaga zakat BASNAZ kabupaten Labuhanbatu Selatan melirik hal tersebut dan melakukan aksi nyata dalam meningkatkan literasi zakat perkebunan kelapa sawit di Kabupaten Labuhanbatu Selatan. Kata Kunci: Literasi, Zakat, BAZNAS